Worship and Theology in England, Volume III : From Watts and Wesley to Maurice - Davies, Horton (Princeton, NJ : Princeton University Press, 2015)
Worship even more than theology may be the key to a true understanding of the Church's history, for through it people express their interpretation of theology and religion. In this third volume (chronologically) of a planned several-volume series, Professor Davies traces liturgy's relationship to music, literature, and architecture; studies the effects of philosophical, social, and theological movements (18th century Rationalism, the Oxford Movement, the Evangelical Revival); and describes the techniques of such popular preachers and teachers as Whitefield and Wesley. There are chapters on Anglican, Congregational, Baptist, Presbyterian, Quaker, and Unitarian worship, forming a rich portrait of the varieties of Christian worship in England.Originally published in 1961.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- ACKNOWLEDGMENTS -- CONTENTS -- ILLUSTRATIONS -- INTRODUCTION -- PART ONE. 1690-1740: THE DOMINANCE OF RATIONALISTIC MORALISM -- CHAPTER I. TWO TRADITIONS OF WORSHIP: ANGLICAN AND PURITAN -- CHAPTER II. GEORGIAN CHURCHES AND MEETING-HOUSES -- CHAPTER III. ANGLICAN WORSHIP AND PREACHING IN THE AUGUSTAN AGE -- CHAPTER IV. UNITARIAN WORSHIP: THE LITURGY OF RATIONALISM -- CHAPTER V. THE OLD DISSENT: INDEPENDENTS AND PRESBYTERIANS -- CHAPTER VI. RADICAL WORSHIP: THE QUAKERS AND THE BAPTISTS -- PART TWO. 1740-1830: THE DOMINANCE OF EVANGELICALISM -- CHAPTER VII. THE METHODIST REVOLUTION IN POPULAR PREACHING: THE TECHNIQUES OF WESLEY AND WHITEFIELD -- CHAPTER VIII. THE METHODIST UNION OF FORMAL AND FREE WORSHIP -- CHAPTER IX. ANGLICAN EVANGELICALISM: THE SPIRIT AND THE LITURGY -- PART THREE. 1830-1850: THE DOMINANCE OF TRADITIONALISM -- CHAPTER X. THE OXFORD MOVEMENT: THE RECOVERY OF CATHOLIC TRADITION -- CHAPTER XI. F. D. MAURICE AND THE LITURGY AS THE SYMBOL OF UNITY IN CHURCH AND STATE -- BIBLIOGRAPHY -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Public worship -- History; Theology -- England -- History; Theology, Doctrinal -- England -- History; RELIGION / Christianity / General